Portable, low-cost, desktop microscope - Vincent Salvadori; Daniel Fäh; Sarina Flühler; Jan Wandeler; Maria J. Jacome; Adrian Koller; Marcel Egli; Simon L. Wuest (HardwareX)
Light microscopes became essential tools in everyday lab work a long time ago. However, most commercial microscopes are costly, and they are often bulky and heavy. Therefore, microscopes are rarely seen in mobile applications or used by interested amateurs. Here, we present an affordable, portable single-lens microscope. It essentially uses a Raspberry Pi single-board computer, a camera, a touchscreen display, and an LED ring at its core. Apart from brightfield microscopy, contrast-enhancing methods by oblique, dark-field, and Rheinberg illumination are possible, as well. The microscope is ideal for applications that do not require high-end optical components. Due to its low cost and flexible use, it is also suitable for hands-on experiences of the fascinating world not visible by the human eye.